Pengaruh Woman On Board Terhadap Carbon Emission Disclosure - Emy Dwi Nursulistyo; Bandi Bandi (Journal Of Business, Finance, and Economics (JBFE), 2023)
This research aims to examine the influence of women on board carbon emission disclosure in the Indonesian non-financial industry. This research is quantitative and uses secondary data in the form of annual reports and/or company sustainability reports for 2019-2021 in the non-financial industry in Indonesia. The population in this research is all companies listed on the IDX in 2019-2021. The research sample consisted of 72 non-financial industrial companies consisting of basic materials, consumer non-cyclical, consumer cyclical, energy, industrial, infrastructure, property and real estate, and transportation and logistics using a purposive sampling method. The research results show that the woman on-board director hypothesis has a positive effect on carbon emission disclosure with a significance value of 0.0000 < 0.05.